붉은사슴과 엘크에서 SRY와 ZFX-ZFY 유전자의 Duplex PCR기법을 이용한 성 판별 - 한상현; 이성수; 고문석; 조인철; Han, S.H; Lee, S.S; Ko, M.S; Cho, I.C (Journal of animal science and technology, 2007)
This study was focused on discriminating the molecular sexes of red deer and elk by duplex polymerase chain reaction(PCR) using two primer sets. Sex differentiation of mammals is primarily dependent on the presence or absence of sex determining region Y(SRY) gene encoded on Y chromosome which plays a key role for male development. Zinc finger X-Y(ZFX-ZFY) gene, one of X-Y homology gene group was found on X- and Y- chromosomes, respectively. At first, the nucleotide sequences were characterized for the intron 9 flanking region of ZFX-ZFY genes. The intron 9 of ZFX and ZFY is 529-bp and 665-bp in length, respectively. A transposable element sequence similar to bovine SINE element Bov-tA was detected only in ZFY gene of Cervidae. Sexing analysis was conducted by duplex PCR assay for amplification of SRY and ZFX-ZFY genes. Two differentially amplified patterns were found: one for females has a common band amplified only from ZFX as a template, and another for males had three bands(a common ZFX and two male-specific ZFY and SRY). On the separate tests using each gene, the results was identical to those from duplex PCR assay. Moreover, the results from PCR assays provide also identical information to phenotypic investigation of individuals of red deer, elk as well as their hybridized progenies collected from two isolated farms. These results suggest that it may be a rapid and precise method for determining the sexes by duplex PCR amplification using Y-chromosome specific SRY and X- and Y- homologous ZFX-ZFY genes showing sexual dimorphism in red deer and elk without any other controls. 두 가지 primer 쌍을 동시에 이용한 duplex PCR 기법으로 붉은사슴과 엘크의 유전자 성 판별에 대한 이용가능성을 확인하기 위해 본 연구를 수행하였다. 근본적으로 포유동물의 성 분화는 Y-염색체 상에 암호화되어 있으며 웅성발생에 지배적인 역할을 수행하는 SRY 유전자의 존재 여부에 따라 결정되게 된다. X-, Y- 염색체에 상동인 유전자들 중 하나인 ZFX-ZFY 유전자는 X-, Y- 염색체 상에서 각각 발견된다. 유전자 성 판별에 앞서 붉은사슴의 ZFX-ZFY 유전자의 인트론 9를 포함하는 절편에 대한 염기서열의 특성을 확인하였다. 인트론 9의 길이는 ZFX와 ZFY에서 각각 529, 665-bp로 확인되었다. ZFY 인트론 9에서 전위인자의 일종인 bovine SINE element와 유사한 서열이 관찰되었다. SRY와 ZFX-ZFY 유전자들을 동시에 증폭하는 duplex PCR을 통해 유전자 성 판별을 수행하였고, 암수가 서로 구분되는 증폭 양상을 나타내었다: 암컷에서는 ZFX에서 증폭된 공통의 증폭 산물 하나만이 관찰되었고 수컷은 세 개의 밴드가 관찰되었다(ZFX에 해당하는 공통의 밴드와 ZFY와 SRY에서 증폭된 두 개의 수컷 특이 밴드). 두 가지 유전자에 대한 독립적인 PCR 시험에서 얻은 결과는 duplex PCR에 의해 얻은 결과와 동일한 양상을 나타내었다. 또한 유전자 성 판별의 결과들은 각각의 개체에 대한 표현형적 성판별 자료와 정확히 일치하였다. Y 염색체 특이적인 SRY와 X-, Y- 상동이면서 성적 이형성을 나타내는 ZFX-ZFY 유전자들에 대한 duplex PCR 방법은 붉은사슴과 엘크의 성 판별에 있어 여타 다른 대조시험을 요구하지 않으면서 없이 신속하고 정확한 정보를 제공하는 분석법이 될 것으로 기대된다.